Positive and negative synergies between the CEO's and the corporate board's human and social capital: A study of biotechnology firms - Sundaramurthy, Chamu; Pukthuanthong, Kuntara; Kor, Yasemin (Strategic Management Journal, 2014)
This paper contributes to the corporate governance literature by developing and testing theory regarding positive and negative synergies between the CEO 's and the board's human and social capital. Using a sample of 360 biotechnology firms that went public between 1995 and 2010, we demonstrate that accumulated public company board experiences of the CEO and the board have positive synergistic effects on IPO performance whereas the current board appointments have negative effects. While scientific educational backgrounds have positive synergies, industry‐specific experiences produce either positive or counterproductive effects depending on the age and profitability of the firm. Thus, our paper contributes to the corporate governance and human and social capital literatures by describing the costs and benefits of specific types and combinations of CEO and board capital . Copyright © 2013 John Wiley & Sons, Ltd.